Angiotensin‐converting enzyme inhibitors‐induced angioedema treated by C1 esterase inhibitor concentrate (Berinert®): about one case and review of the therapeutic arsenal. Issue 2 (5th December 2014) - Lipski, Samuel Michael; Casimir, Georges; Vanlommel, Martine; Jeanmaire, Mathieu; Dolhen, Pierre
<x xml:space="preserve">Abstract</x> C1 esterase inhibitor (Berinert®) is generally used to treat severe attack of hereditary angioedema. We describe here the case of a patient who presented with a severe angioedema induced by angiotensin‐converting enzyme inhibitors (ACEIs) endangering her life. It could be successfully treated with that medicine. <boxed-text content-type="graphic" id="ccr3171-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>